Study on pH Sensor Device using Conventional and Plasma Treated pH Sensor - Nadeson, Malarvili; Nayan, Nafarizal (Evolution in Electrical and Electronic Engineering, 2021)
Every living thing on Earth requires water to survive. Water supplies to taps in urban residences and water sources available in more rural areas, on the other hand, are not always suitable for drinking. In this project, plasma treatment was used on the surface of the pH sensor to monitor the difference in pH measurements between treated and untreated sensors to evaluate the accuracy of a pH sensor before and after plasma treatment. The plasma treatment is used to treat the sensitive glass membrane of the pH sensor in the Atmospheric pressure plasma needle jet (APPJ). The sensor undergoes surface plasma treatment and measures the pH value of five different samples in a proposed prototype. From the Arduino, the information is passed to the microcontroller and transferred to the android application, and show the result in excel through PLX-DAQ platform. Finally, the accuracy will be determined by comparing the data from treated and untreated sensors. The most suited sensor for monitoring the pH value is a conventional sensor. According to the results of the experiment, an untreated sensor reads more accurately than a treated sensor. Furthermore, data from an untreated sensor is not delayed. The reading was obtained sooner than the treated sensor. As a consequence, it is acceptable to conclude that an untreated sensor is preferable to a treated sensor. Apart from plasma treatment, have new approaches such as atomic force microscopy AFM or X-ray diffraction analysis XRD techniques.